Сraniotopografic features of dural venous formations. - O. Y. Vovk; Y. V. Boguslavskiy; A. O. Shmarhalov (Морфологія, 2016)
Background. Morphometric and cranial-topographic features of venous structures of dura mater and their relationships have important clinical implications, especially in the field of neurosurgery and neuroscience, diagnostics of diseases. Objective. The aim of the study is to establish the characteristics of dural venous formations and their anatomical variability. Methods. This study was performed on the corpses of people of different age and sex with the production of the native brain preparations with meninges. We have made 70 specimens of dura mater with its derivatives, which were subjected to morphometric analysis with the examination of a number of indicators. The cranial index was pre-calculated to determine the constitutional head type. Results. It is found that in the superior sagittal sinus (SSS) on each side there could be from 6 to 12 tributaries – superficial cerebral veins forming different venous networks. Depending on the development of anastomoses it was established two extreme forms of SSS structure: abundantly anastomosing and with low anastomoses. Additionally several structural forms of the transverse sinuses were subdivided: extended symmetric; extended asymmetric; narrow symmetric and asymmetric narrow. Conclusions. The morphometric characteristic has revealed a refined localization of venous collectors comparing with common cranial points in the sagittal, frontal and horizontal planes.